ANALISIS PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DESA MALANG RAPAT DALAM PERSPEKTIF ISLAM - Muhammad Imaaduddin; Masjunaidi (STAI Miftahul Ulum Tanjungpinang, 2023)
This research was conducted to find out the types of businesses managed by the Management of Village-Owned Enterprises (Bumdes) in Malang, Gunung Kijang District, and the problems that resulted in the non-performance of descriptive qualitative research methods. Data collection is in the form of observation, interviews and documentation. From the results of this study it can be concluded that the businesses managed by the Malang Village-owned Enterprises, Gunung Kijang District, namely: Bumdes Brokering & Serving, Bumdes Trading solutions to overcome Bumdes businesses that are not developing in society must have other creative ideas that can be developed in the village. Malang Meeting in Gunung Kijang Sub-District The positive impacts of Bumdes activities are increasing the economy, welfare and improving people's health, in addition to providing jobs and reducing unemployment. The negative impact is the higher the competition in the environment around the Bumdes. Then the role of the Village Officials is also important for the existence of the Bumdes in Malang Meeting Village, Gunung Kijang District. In channeling time, energy and thoughts so as to create activities that suit the needs of the community.